Metal-enhanced fluorescence in liposomes for photothermal studies - Lee, Elizabeth Mei Yin (2013)
Metal-dye interaction studies have shown either an enhancement or quenching of a dye by metal nanoparticles. If the separation distance between the metal and dye molecule is smaller than the Forster distance, there is quenching due to the damping of dipole oscillation coupled to surface plasmon modes. For separation distances larger than the Forster distance but still within the magnitude of the metal nanoparticle size, there is enhancement of emission intensity due to local field enhancement of metal nanoparticles. Liposomes are lipid vesicles with an aqueous core capable of encapsulating dye molecules. Upon heating above transition temperature, the membrane becomes leaky, enabling the contents to diffuse out of the liposome. [4th Award]